FENOMENA PEKERJA ANAK USIA SEKOLAH: PEDAGANG ASONGAN ANAK DI PALANGKA RAYA - Yuseva; M. Husin Saputra; Sonia Sakira; Saputra Adiwijaya; Osi Karina Saragih (Prodi Sosiologi FISIP UPR, 2024)
The phenomenon of school-aged children engaging as street vendors reflects social inequality and economic pressures that compel them to work at an early age. This study aims to explore the factors that drive children’s involvement in economic activities and to examine the impacts on their social lives, education, and psychological well-being. Employing a descriptive qualitative approach, data were collected through literature review, interviews, observations, and documentation, focusing on child street vendors in Palangka Raya City. The findings indicate that poverty, low parental education, limited awareness of children’s rights, and weak supervision by social institutions are the main driving factors. These children face significant challenges in balancing their dual roles as students and breadwinners, leading to the neglect of their fundamental rights such as access to education, healthcare, and leisure. The study underscores the urgent need for cross-sectoral attention and intervention to prevent exploitation and to ensure the comprehensive protection and fulfillment of children’s rights.